Bank specific and economic factors on bank's non-interest based activities in Asia Pacific banking - Koh, Chin Wei; Ab Razak, Nazrul Hisyam; Kamarudin, Fakarudin; Cheng, Fan Fah (Panoply Consultancy, 2017)
This study investigates bank specific and economic factors on bank non-interest based activities in Asia Pacific region banking sector over the years 2000-2015. We employ the pooled OLS and panel regression to assess the bank specific and economic factors effect on bank non-interest based activities through 61 representative banks from Australia, Hong Kong, Korea, Malaysia, Singapore and Thailand in Asia Pacific region. The empirical findings indicate that the bank specific and economic do have impact on developing and developed countries respectively. We also find that the non-interest based activities also affected by subprime crisis for developed and developing countries. The findings from this study are expected to contribute significantly toward decision-making for regulators, policymakers, bank managers, investors, and also to the existing knowledge on performance of the Asia Pacific banking sector.